Genotoxic evidences of glyphosate and chlorpyriphos on eisenia fetida coelomocytes - Curieses, Silvana Patricia (2018)
The organophosphorus herbicide glyphosate (GLY) and the organophosphate insecticide chlorpyriphos (CPF) are key pesticides in modern management cultures worldwide. Sublethal toxicity of the commercial herbicide formulation Roundup® and the insecticide formulation Terfos® were evaluated on Eisenia fetida coelomocytes exposed under in vivo and ex vivo laboratory conditions. Induction of DNA single-strand breaks evaluated by the single cell gel electrophoresis assay and coelomocyte viability as well as alterations in coelomocyte trophic indexes were employed as endpoints for genotoxicity and cytotoxicity, respectively. Specimens were exposed at concentrations corresponding to recommended pesticide field application rate, and endpoints were evaluated after 7 and 14 days of treatment (in vivo exposure). In addition, coelomocytes were exposed to aqueous leachate of pesticide-contaminated soils during 1 h (ex vivo exposure). Earthworms exposed to Roundup® and Terfos® showed an increased frequency of DNA damage. Also, a decrease of coelomocyte viability and decrease of trophic indexes were observed in all treatments. The results demonstrate that either GLY- and CPF-based formulations exerted genotoxic as well as cytotoxic effects in coelomocytes of E. fetida exposed in vivo and ex vivo.